2017
DOI: 10.1016/j.fuproc.2017.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Secondary comminution of wood pellets in power plant and laboratory-scale mills

Abstract: This study aims to determine the influence of mill type and pellet wood composition on particle size and shape of milled wood. The size and shape characteristics of pellets comminuted using power plant-scale roller-and hammer mills were compared with those obtained by using a laboratory-scale roller mill. A 2D dynamic imaging device was used for particle characterization. It was shown that mill type has a significant impact on particle size but an almost negligible effect on the shape of milled wood. Comminuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
(20 reference statements)
3
9
0
Order By: Relevance
“…The Feret maximal diameter, representing the length, is greater than the width. Therefore, the Martin minimal (x Ma min ) and Feret maximal (x Fe max ) diameters are suitable parameters to represent the width and length of biomass particles, confirming previous results of Trubetskaya et al [29]. The most suitable descriptor of particle size, when characterized using sieving and 2D dynamic imaging, is the smallest maximal chord (x c min ) [19].…”
Section: Particle Size Analysissupporting
confidence: 82%
“…The Feret maximal diameter, representing the length, is greater than the width. Therefore, the Martin minimal (x Ma min ) and Feret maximal (x Fe max ) diameters are suitable parameters to represent the width and length of biomass particles, confirming previous results of Trubetskaya et al [29]. The most suitable descriptor of particle size, when characterized using sieving and 2D dynamic imaging, is the smallest maximal chord (x c min ) [19].…”
Section: Particle Size Analysissupporting
confidence: 82%
“…The Camsizer ® definition of the circularity is the ISO 9276-6:2008 standard definition squared [35]. Both shape factors are commonly used for describing comminuted wood particle shapes [12,17]. The aspect ratio (AR) ranging between zero and one is defined as follows:…”
Section: Pellet Milling Behaviormentioning
confidence: 99%
“…Regarding the particle shape, Trubetskaya et al [12] found no difference between roller-milled and hammer-milled particles. However, roller mills required less power for grinding than hammer mills [12,13]. The energy needed for milling biomass depends on the feed moisture, particle size reduction ratio, feedstock characteristics [14], feed rate and mill operating parameters [15].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations